Overview of X-ray laser research in the UK - Lewis, C; Keenan, R; MacPhee, A; O'Rourke, R; Tallents, G; Eker, G; Lin, J; Pestehe, S; Smith, R; Wark, J; Wolfrum, E; Zhang, J; et al. (1999)
Developments in collision-pumped X-ray lasers using a variety of pumping configurations made possible by the versatile VULCAN glass laser at the Central Laser Facility are described. Optimised pumping configurations for nickel-like ions in the QSS regime has lead to saturated outputs at wavelengths as low as 5.8 nm and CPA technology has enabled travelling wave pumping in the TCE regime to deliver saturated output at 12.0 nm, from nickel-like tin. New directions, stemming from availability of more intense pumps and brighter XRLs are discussed briefly.